Evidence from 617 laboratories in 47 countries for SLMTA-driven improvement in quality management systems - Katy Yao; Elizabeth T. Luman; SLMTA Collaborating Authors (AOSIS, 2014)
Background: The Strengthening Laboratory Management Toward Accreditation (SLMTA) programme is a large-scale effort to improve the quality of laboratories in resource-limitedcountries. Objectives: This study sought to evaluate the first four years (2010-2013) of SLMTA implementation. Methods: Country-level data were submitted by SLMTA programme leads and compiledglobally. Performance was measured before (baseline) and after (exit) SLMTA implementation using an audit checklist which results in a percentage score and a rating of zero to five stars. Some laboratories continued to monitor performance in post-exit surveillance audits. We evaluated score improvements using two-tailed t-tests for equal variances and estimated the number of tests performed by SLMTA laboratories based on star level. Results: SLMTA was implemented in 617 laboratories in 47 countries in Africa, the Caribbean, Latin America and Southeast Asia. At the baseline audit, the laboratories scored an average of 39% on the checklist and 84% of them were rated below one star. As of December 2013, 302 laboratories had completed the SLMTA programme; mean checklist scores increased from39% at baseline to 64% at exit (p < 0.001) over an average 16-month programme duration. Ninety-two laboratories conducted a surveillance audit at a median of 11 months after their exit audit; 62% further increased their performance. Six SLMTA laboratories have achieved accreditation status. In total, the 617 SLMTA laboratories conduct an estimated 111 milliontests annually. Only 16% of these tests were conducted by laboratories with at least one star at baseline, which increased to 68% of tests after SLMTA training. Thus, approximately 23 million tests are conducted annually by laboratories previously at zero stars that now have one to five stars; this number is projected to increase to 58 million when currently-enrolled laboratories complete the programme. Conclusion: SLMTA has transformed the laboratory landscape in resource-limited countries worldwide and has the potential to make a substantial and sustainable impact on the qualityof laboratory testing and patient care.